Analysis of the Factors Behind the Persistent Cattle Rustling in Karamoja Sub Region in Relation to Its Dwindling Development - Samuel Lokong (Uganda Christian University, 2024)
This study aimed at analyzing the factors behind the persistent cattle rustling in Karamoja Sub-region. It looked at; the causes of cattle rustling in Karamoja Sub-region, the effects of cattle rustling on the people of Karamoja Sub-region and the effectiveness of the measures the government uses to address the problem of cattle rustlint in Karamoja Sub-region. As a way of obtaining data from the local people on the study topic, the questionnaire was designed with probing questions on the study topic. It was found out that the causes of cattle rustling in Karamoja Sub-region are; uncontrolled flow of small firearms, high value put on cattle, high bride wealth, search for power and fame, enmity among the major tribes within Karamoja Sub-region. Furthermore 70% of the respondents when interviewed attributed the persistent cattle rustling in Karamoja Sub-region to high level of illiteracy among the Karamojongs and influence from the witch doctors that encourages the Karamojong young men to go for raiding with a claim that their pronouncements and charms make them successful and protected in case of any resistance. On the effects of cattle rustling on the people of Karamoja Sub-region, high death rate, poverty, displacement of settlements and development hindrance were found to be the effects of cattle rustling on the people of Karamoja Sub-region. The study also carried out an assessment on the effectiveness of the measures the government uses in addressing the problem of cattle rustling in Karamoja Sub-region and as a result, 34% of the targeted respondents said the measures that the government uses in addressing the problem of cattle rustling in Karamoja Sub-region are not effective at all, 52% said they were partially effective while 14% said the measures were effective.
Undergraduate research